Legal Certainty Of Trademark Registration To Improve The Welfare Of Micro, Small And Medium Enterprises (Msmes) - Saka, Risti; Santiago, Faisal (Riviera Publishing, 2024)
Micro, Small and Medium Enterprises (MSMEs) hold role important in the Indonesian economy, but they often face challenge in protect asset intellectual, especially brand. Uncertainty law in registration brand cause risk piracy and its impact negative on power competition as well as sustainability UMKM business. Research This aiming For explore certainty law in registration brand for MSMEs in Indonesia and evaluate the impact to welfare economy UMKM actors. Research This use approach law empirical, conducted in several city with high UMKM population, Data collection techniques were carried out with method survey and observation field, and semi- structured interview. Research results show that although registration brand give protection significant for MSMEs and improve Power competition they, still there is constraint in accessibility, understanding law, and costs. Implications from study This underline importance role government in give education, simplifying the registration process, and providing support financial for MSMEs. With existence more policies? inclusive, MSMEs are expected can protect brand they in a way effective, which ultimately strengthen economy local and national.